Power and Categorization: Power Increases the Number and Abstractness of Categories. (April 2016) - Smith, Pamela K.; Smallman, Rachel; Rucker, Derek D.
Across three experiments, participants formed a larger number of categories when in a state of high, compared to low, psychological power. Moreover, in contrast to prior categorization research, which suggests forming more categories is tantamount to reduced breadth of categorization, high-power participants also formed a larger number of superordinate (i.e., more abstract) categories than low-power participants. The present findings enhance the understanding of power in relation to categorization and simultaneously highlight the distinction between number and abstraction as fundamental aspects of categorization.